Sanctions as Tool for Strategic Deterrence: An Assessment of Targeted Sanctions in Russia - Amaechi Fidelis Nwador; Franklins A. Sanubi; Esekumemu Victor Clark (Universitas Medan Area, 2023)
Strategic deterrence through the use of sanctions in the international system is gaining support among major players. This is despite widespread scepticism over the instrument's efficacy, as seen by the widespread opposition to its use immediately following its implementation in Iraq in the immediate aftermath of the end of the Cold War. The takeover of Ukraine is the first opportunity since World War II to analyse the results of sanctions on a major power and permanent member of the UN Security Council. The issue raises the question of whether or not sanctions on Russia would be an effective strategy in stopping their aggressiveness in Ukraine. In this article, we analyse how targeted sanctions against Russia's economy can alter the course of the conflict in Ukraine. Given the energy linkages that most of these governments have with Russia, we see the sanctions' proponents the United States, the European Union, and the Baltic States suffering increasingly negative consequences. We also contextualise the acts of sanction busters empowered by the United States' inability to develop a consensus at the United Nations General Assembly and by Russia's veto to thwart the criminalization of their conduct in the United Nations Security Council. Despite this, it is becoming apparent that Russia's economy is feeling the effects of the sanctions, which is substantially diminishing their ability to properly prosecute the war. Methodologically, the study used a historical approach, meaning that it relied on information gathered from previously existing sources including encyclopaedias, encyclopaedia articles, and news stories. In conclusion, the data appears to bolster the view that the possible risk spawned in the harsh reality of targeted or comprehensive sanctions on Russia given the extent of the punishment regime is an acceptable price for the maintenance of the rule-based international order.